2018
DOI: 10.1016/j.neo.2018.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the Immune Checkpoint Modulator OX40 in Acute Lymphoblastic Leukemia Is Associated with BCR-ABL Positivity

Abstract: OX40 and its ligand are members of the TNF/TNF receptor superfamily, which includes various molecules influencing cellular signaling and function of both tumor and immune cells. The ability of OX40 to promote proliferation and differentiation of activated T cells fueled present attempts to modulate this immune checkpoint to reinforce antitumor immunity. While we recently found evidence for the involvement of OX40 in pathophysiology of acute myeloid leukemia including natural killer (NK) cell immunosurveillance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 48 publications
0
12
0
Order By: Relevance
“…Also, the high or low expression status was related to mutations in AKT/mTOR and Wnt/ β-catenin signaling, respectively. The OX40 expression was also associated with poor prognosis and shorter survival in the study of acute myeloid leukemia (54). In nearly half of the cases, OX40 expression led to proliferation and release of proleukemic cytokines, which provided a survival benefit for leukemic cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, the high or low expression status was related to mutations in AKT/mTOR and Wnt/ β-catenin signaling, respectively. The OX40 expression was also associated with poor prognosis and shorter survival in the study of acute myeloid leukemia (54). In nearly half of the cases, OX40 expression led to proliferation and release of proleukemic cytokines, which provided a survival benefit for leukemic cells.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, it is the first research to analyze the role of OX40/OX40L in early-stage resectable NSCLC and demonstrate its relationships with PD-1/PD-L1, TILs and patients' clinical outcomes. OX40/OX40L has already been studied previously as an immune characteristic biomarker in some other cancer types, including lymphoma, hepatocellular carcinoma, Leukemia, ovarian, neuroblastoma, head and neck squamous cell carcinoma, gastric cancer and breast cancer (52)(53)(54)(55)(56)(57)(58)(59)(60)(61)(62)(63). The TILs OX40 was reported to correlate with patient survival.…”
Section: Discussionmentioning
confidence: 99%
“…Xie et al discovered that in hepatocellular carcinoma, the higher OX40 expression in TILs correlated with poor survival [ 14 ]. Similarly, in myeloid leukemia, shorter survival was related to OX40 expression while in patients with an early stage of “non-small cell lung carcinoma” (NSCLC), higher TIL OX40L expression had a poor prognosis [ 15 - 16 ]. On the contrary, lower OX40 expression was correlated with chemosensitivity as well as recurrence-free survival in ovarian cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…Xie et al [23] found that high OX40 expression in TIL hepatocellular carcinoma correlates with poor survival. Rothfelder et al [24] reported that OX40 expression was related to shorter survival in myeloid leukemia. Recently, He et al [20] demonstrated that patients in the early stage of NSCLC with a high OX40L expression in TIL had poor prognosis.…”
Section: Discussionmentioning
confidence: 99%